Method for manufacturing a multilayer board
By using high molecular weight glyoxylated polyacrylamide as a chemical additive in the manufacture of multilayer boards, the problem of strength reduction caused by the recycling of cellulose fibers is solved, and the internal and interlayer bonding properties of multilayer boards are improved, especially in terms of strength and anti-delamination in the z-direction.
Patent Information
- Application Number
- CN202480020572.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-03-21
- Filing Date
- 2024-03-20
- Publication Date
- 2025-11-14
AI Technical Summary
In the prior art, the recycling of cellulose fibers leads to a reduction in fiber length and surface charge, resulting in a decrease in the internal strength and interlayer bonding performance of multilayer boards, especially in terms of strength and anti-delamination in the z-direction.
In the manufacturing process of multilayer boards, glyoxylated polyacrylamide with a number average molecular weight of at least 15,000 g/mol is used as a chemical additive, which is added separately or together to the first and second fiber suspensions to improve the bonding strength between fibers and the resistance to delamination.
It significantly improves the internal strength and interlayer bonding performance of multilayer boards in the z-direction, reduces the risk of delamination and splitting, and enhances the overall strength and delamination resistance of multilayer boards.
Smart Images

Figure BDA0005605044540000041 
Figure BDA0005605044540000131 
Figure BDA0005605044540000151
Abstract
Description
Technical Field
[0001] The present invention relates to a method for manufacturing a multilayer board according to the preamble of the appended independent claims. Background Technology
[0002] Board, especially corrugated board, is one of the most widely used packaging materials in the world due to its low cost, lightweight structure, and recyclability. Corrugated board typically consists of at least one corrugated sheet of grooving board, which is bonded to one or two flat facing sheets. To obtain the optimal strength, stiffness, and bulk required for different end-use applications, grooving and facing boards are often manufactured in multi-layer structures. Each layer may contain different chemical additives and / or different fibers, i.e., fibers with different lengths and / or originating from different sources. For example, facing boards are often manufactured by using long fiber portions for the top layer and short fiber portions for the back layer. In this way, the performance of each layer, as well as the performance of the multilayer board itself, can be optimized.
[0003] Recycled cellulose fibers from various sources are commonly used in the manufacture of plywood. Over the past few decades, the recycling rate of cellulose fibers has been continuously increasing. Each time cellulose fibers undergo a repulping process, their fiber length typically shortens, and their anionic surface charge decreases. This means that with increasing recycling, the average fiber length of both the long and short fiber portions decreases. Simultaneously, the anionicity of the surface charge on recycled cellulose fibers becomes less. Shorter fiber lengths negatively impact the strength of plywood, while less anionic fiber surface charge reduces the interaction between the cellulose fibers and the chemical additives used in the manufacture of the plywood.
[0004] Over the past few decades, process water circulation in board manufacturing has become increasingly closed. This means introducing minimal amounts of fresh water into the manufacturing process and recycling used water within the process as much as possible. Most commonly, closed process water circulation leads to an increased amount of dissolved anionic charged substances in the process water.
[0005] Due to the aforementioned developments, fiber suspensions used in board manufacturing often contain recycled cellulose fibers with short fiber lengths and low surface charges, along with an aqueous phase rich in anionicly charged interfering substances. This can lead to reduced efficiency of common papermaking chemical additives, such as glyoxylated polyacrylamide, obtained by polymerizing acrylamide and cationic monomers and then crosslinking the polymer with glyoxal. The function of papermaking chemicals is typically based on the electrostatic interaction between the cationic charged groups of the chemicals and the anionic groups on the surface of the cellulose fibers. When using recycled fibers, it has been observed that the desired effect of the chemical additive dosage is not always achieved. It is speculated that the uncharged surface of the cellulose fibers, coupled with the potentially high charge load in the aqueous phase, negatively impacts the expected interaction between the chemical additives and the recycled fibers. This reduction in interaction can lead to decreased strength in multilayer boards, etc. Multilayer boards may exhibit reduced internal strength in the z-direction, manifested as delamination or splitting, either at the boundaries between layers or within a single layer. Therefore, a method is needed to produce multilayer paperboards, such as grooved or linerboard, with improved internal strength, even from recycled fibers. Summary of the Invention
[0006] One object of the present invention is to minimize or even eliminate the disadvantages present in the prior art.
[0007] Another object of the present invention is to provide a method for improving the internal strength properties of multilayer boards, particularly the internal strength in the z-direction within each layer and the interlayer strength, such as interlayer bonding.
[0008] Another object of the present invention is to provide a method for improving the anti-delamination properties of the layers of a multilayer fiber mesh or board.
[0009] These objectives are achieved by an invention having the features set forth in the characterizing portions of the following independent claims. Some preferred embodiments of the invention are given in the dependent claims.
[0010] The embodiments mentioned herein relate to all aspects of the invention where applicable, even if these aspects are not always mentioned separately.
[0011] In a typical method according to the invention for manufacturing multilayer boards in a board machine, the multilayer board comprises at least two layers, the method comprising:
[0012] - Obtain a first fiber suspension containing cellulose fibers for a first layer and a second fiber suspension containing cellulose fibers for a second layer, wherein the first fiber suspension and the second fiber suspension are different from each other, and at least one of them contains recycled cellulose fibers;
[0013] -A first layer is formed by a first fiber suspension, and a second layer is formed by a second fiber suspension.
[0014] - By combining the first and second layers together, a multi-layered board web is formed, which is then wet-pressed in the press section of the paperboard machine.
[0015] -Dry multi-layer boards
[0016] Specifically, before forming the first and second layers, glyoxylated polyacrylamide with a number average molecular weight of at least 15,000 g / mol is added to the first fiber suspension and / or the second fiber suspension.
[0017] It has now been surprisingly discovered that adding glyoxylated polyacrylamide with a number-average molecular weight of at least 15,000 g / mol can significantly improve the internal strength of the formed layer in the z-direction and improve the delamination resistance of the multilayer board. It is speculated that when the number-average molecular weight is as defined in this invention, the glyoxylated polyacrylamide will not be consumed by harmful interactions with anionic interfering substances in the aqueous phase of the suspension and can effectively interact with the sparse anionic charges on the fiber surface. Glyoxylated polyacrylamide with a number-average molecular weight of at least 15,000 g / mol can improve the internal strength of the formed layer, and even the strength between two layers, i.e., the interlayer adhesion and strength between the first and second layers. Typically, the z-direction strength is weakest at interlayer boundaries, but according to this invention, adding specific glyoxylated polyacrylamide can significantly reduce the risk of splitting or delamination in multilayer boards. It is speculated that when the number-average molecular weight of the glyoxylated polyacrylamide is sufficiently high, a sufficient amount of polymer can cross the boundaries of adjacent layers. In general, according to this invention, the internal strength in the z-direction between layers (i.e., at the boundaries between two layers) and within a single layer can be improved. The improvements obtained can be demonstrated, for example, by Scott Bond, z-direction strength and / or peel force measurements.
[0018] In this context, number-average molecular weight represents the statistical average molecular weight of the polymer chain and is defined as:
[0019]
[0020] Among them, M i It is the molecular weight of the chain, and N i It represents the chain number for that molecular weight.
[0021] Improvements in the internal z-direction strength of multilayer boards can be described by measuring their Scott Bond and / or z-direction tensile strength. According to the method of the present invention, the Scott Bond and / or z-direction tensile strength of multilayer boards are improved. Improved internal z-direction strength typically leads to improved SCT strength results when buckling of the multilayer board is reduced or even absent in SCT tests due to weak internal bonding.
[0022] A multilayer board comprises at least two fiber layers, namely a first layer and a second layer. Possibly, the multilayer board may include one, two, or more additional intermediate layers located between the first and second outer layers. For example, the multilayer board sheet may be a testliner or a whitetop liner, comprising two fiber layers. The testliner may comprise long-fiber recycled pulp as a top layer (first layer) and short-fiber recycled pulp as a back layer (second layer). The whitetop liner may comprise bleached kraft pulp (e.g., short-fiber or mixed office waste recycled pulp) as a top layer (first layer) and unbleached kraft pulp and / or recycled pulp as a back layer (second layer). According to one embodiment, the multilayer board may comprise a total of 2-5 layers, preferably 2-4 layers. The number of layers in the multilayer board is not limited, and the method according to the invention is applicable to all types of multilayer boards, regardless of the number of layers. For example, the multilayer board may comprise three layers: a first layer and a second layer forming the outer layers, and an additional intermediate layer located between the first and second (outer) layers. The first and second outer layers form the large surface of the multilayer board.
[0023] According to a preferred embodiment of the invention, the number average molecular weight of the glyoxylated polyacrylamide can be at least 20,000 g / mol, preferably at least 25,000 g / mol, and more preferably at least 30,000 g / mol. The number average molecular weight can be, for example, in the range of 15,000-250,000 g / mol, preferably 20,000-200,000 g / mol, more preferably 25,000-150,000 g / mol, and even more preferably 30,000-100,000 g / mol. When the glyoxylated polyacrylamide has a number average molecular weight of at least 15,000 g / mol or higher, it means that the glyoxylated polyacrylamide contains fewer oligomers or lower molecular weight polymer materials. The absence of low molecular weight or low-molecular-weight polyacrylamide increases the binding efficiency between cellulose fibers because they do not consume the scarce surface charge on the fiber surface. A number-average molecular weight of at least 15,000 g / mol can also provide effective adhesion between adjacent layers in a multilayer board, i.e., effective adhesion between the first and second layers or between the first layer, an additional intermediate layer, and the second layer.
[0024] The weight-average molecular weight of the glyoxylated polyacrylamide used in this invention can be in the range of 200,000-950,000 g / mol, preferably 250,000-900,000 g / mol.
[0025] In this application, the number-average molecular weight (Mn) and weight-average molecular weight (Mw) were determined by size exclusion chromatography (SEC) using an Agilent 1100SE chromatographic instrument with an integrated pump, autosampler, and degasser. The eluent was buffer (0.3125M CH3COOH + 0.3125M CH3COONa) at a flow rate of 0.5 mL / min at 35 °C. Typical sample concentrations were 2–4 mg / mL, and injection volumes were 50 μL. Ethylene glycol (1 mg / mL) was used as a flow marker. The column setup consisted of three columns (one TSKgel PWXL guard column and two TSKgel GMPWXL columns). Detection was performed using an Agilent refractive index detector (T = 35 °C). Molecular weights were determined using standard column calibration with the Polymer Standards Service for Poly(ethylene oxide) / poly(ethylene glycol) narrow molecular weight distribution standards.
[0026] The glyoxylated polyacrylamide used in this invention can be formed by crosslinking the base polymer of the cationic polyacrylamide with glyoxal. The base polymer can be obtained by polymerizing (meth)acrylamide with 7-50 mol-% (preferably 7-30 mol-%, more preferably 11-25 mol-%) of a cationic monomer. The cationic monomer can be selected from diallyl dimethylammonium chloride (DADMAC), 3-(acrylamidopropyl)trimethylammonium chloride (APTAC), 3-(methacrylamidopropyl)trimethylammonium chloride (MAPTAC), or any combination thereof. Preferably, the cationic monomer is diallyl dimethylammonium chloride (DADMAC). The weight-average molecular weight of the base polymer of the cationic polyacrylamide can be in the range of 30,000-250,000 g / mol, preferably 50,000-200,000, for example 70,000-180,000 g / mol. The weight-average molecular weight of the base polymer describes the molecular weight of the (meth)acrylamide polymer backbone, which is the result of copolymerization of (meth)acrylamide and the cationic monomer. The backbone is substantially linear. Methods for measuring weight-average molecular weight are well known to those skilled in the art, such as size exclusion chromatography (SEC) as described above.
[0027] The base polymer can be acetaldehyde-treated in a chemical plant and then transported to a board-making plant, or it can be acetaldehyde-treated on-site at the board-making plant. The acetaldehyde treatment of the cationic polyacrylamide base polymer is known to those skilled in the art. The total glyoxal content (including free and reacted glyoxal) in the acetaldehyde-treated polyacrylamide used in this invention, calculated based on the total amount of glyoxal and polyacrylamide, can be in the range of 5-25% by weight, preferably 7-21% by weight, more preferably 9-18% by weight, and even more preferably 10-17% by weight. This total glyoxal content reduces the amount of free glyoxal in the acetaldehyde-treated polyacrylamide used.
[0028] The glyoxylated polyacrylamide used in this invention is cationic. Measured at pH 7, the charge density of the glyoxylated polyacrylamide can range from 0.4 to 2.5 meq / g, preferably 0.7 to 2.2 meq / g, more preferably 0.9 to 2.0 meq / g, and even more preferably 1.0 to 1.7 meq / g. Charge density measurements were performed using a Mütek PCD 03. When the charge density of the glyoxylated polyacrylamide is within the defined range, a significant improvement in the internal strength in the z-direction (such as SCT and burst strength) is observed, especially when the fiber suspension contains recycled fibers, such as OCC pulp. Furthermore, the defined charge density range appropriately preserves the glyoxylated polyacrylamide without excessively consuming available anionic charged groups or risking over-cationization of the fiber suspension.
[0029] Each layer of the multilayer board is formed from a fiber suspension containing cellulose fibers. The first layer is formed from a first fiber suspension, the second layer from a second fiber suspension, and any additional intermediate layers are formed from additional fiber suspensions. At least the first and second fiber suspensions are different from each other, and at least one of them (preferably both) contains recycled cellulose fibers. If any additional fiber suspension is used for an additional intermediate layer, the additional fiber suspension is preferably different from the first and second fiber suspensions and may contain recycled cellulose fibers.
[0030] According to one embodiment, the multilayer board may comprise at least three layers, wherein a first layer forms a first outer layer, a second layer forms one of additional intermediate layers, and a third layer forms a second outer layer, which may be the same as or different from the first outer layer. At least the first and second fiber suspensions are different from each other, and at least one of them (preferably both) contains recycled cellulose fibers.
[0031] In this context, the term "fiber suspension" is generally understood to mean an aqueous suspension comprising cellulose fibers and optional fillers. At least one (preferably two or all) of the fiber suspension comprises or consists of recycled fibers. The recycled fibers may be derived from old corrugated cardboard (OCC) pulp, mixed waste (MXW) pulp, old newsprint (ONP) pulp, pulp from household waste collection, pulp from paper containing newsprint and magazines (ONP / OMG), mixed office waste (MOW) pulp, deinked pulp (DIP), or any mixture thereof. According to one embodiment of the invention, the recycled fibers may comprise undeinked recycled fibers. In this context, the term "recycled fibers" should also be understood to encompass broke paper, which is recycled back to the pulping stage from subsequent process stages (such as the web forming stage) within the board mill. The fiber suspension may also comprise cellulose fibers obtained by mechanical pulping, kraft paper pulping, or chemithermomechanical pulping.
[0032] According to one embodiment of the invention, the cellulose fibers in the first fiber suspension may have a first length-weighted average length, and the cellulose fibers in the second fiber suspension may have a second length-weighted average length, which are different from each other. This means that the fiber suspension is prepared by grading the cellulose fibers into at least two different fiber fractions with different length-weighted average lengths, and by preparing the first and second fiber suspensions using the different fractions. The first and second length-weighted average lengths can have a difference in the range of 0.1-1.5 mm, as measured using a Kajaani FSA fiber length analyzer. This means that the first fiber suspension and thus the first fiber layer can contain short cellulose fibers, while the second fiber suspension and correspondingly the second fiber layer can contain longer cellulose fibers. For example, the first length-weighted average length can be in the range of 0.8-1.2 mm, and the second length-weighted average length can be >1.2 mm to 2.0 mm, as measured using a Kajaani FSA fiber length analyzer. According to another embodiment, for example when the fiber suspension contains American Used Corrugated Cardboard (AOCC) pulp, the first length-weighted average length can be in the range of 1.0-1.5 mm and the second length-weighted average length can be >1.5 mm to 2.5 mm, as measured by using a Kajaani FSA fiber length analyzer.
[0033] According to one embodiment, as measured according to standard ISO 5267-2:2001, the first fiber suspension may have a Canadian standard free concentration (CSF) < 120 ml, and the second fiber suspension may have a Canadian standard free concentration (CSF) > 120 ml. Alternatively, as measured according to standard ISO 5267-2:2001, the first fiber suspension may have a Canadian standard free concentration (CSF) < 250 ml, and the second fiber suspension may have a Canadian standard free concentration (CSF) > 250 ml.
[0034] Glyoxylated polyacrylamide with a number-average molecular weight of at least 15,000 g / mol can be added to the first, second, and / or any additional fiber suspensions. According to one embodiment of the invention, glyoxylated polyacrylamide can be added to the first fiber suspension, the second fiber suspension, or any additional fiber suspension used for any additional fiber layer. Alternatively, glyoxylated polyacrylamide can be added to the first fiber suspension, the second fiber suspension, and any additional fiber suspension used for any additional fiber layer. The fiber suspensions in which glyoxylated polyacrylamide is added are freely selectable, thereby increasing the flexibility to adjust the addition to suit each fiber suspension used. For example, glyoxylated polyacrylamide can be added only to a fiber suspension containing short cellulose fibers, the length-weighted average length of which, as measured using a Kajaani FS fiber length analyzer, is <1.5 mm, preferably <1.2 mm. When glyoxylated polyacrylamide is added to a fiber suspension containing short fibers, the increase in z-direction strength achievable with each dosage of polyacrylamide can be maximized. Alternatively, if glyoxylated polyacrylamide is added to a fiber suspension containing long fibers, and the length-weighted average length of the long fibers is >1.5 mm, preferably >1.7 mm, as measured using a Kajaani FS fiber length analyzer, the absolute z-direction strength effect achievable with each dose of polyacrylamide can be maximized.
[0035] Measured at 525°C according to standard ISO 1762, the ash content of the first and / or second fiber suspensions, and any additional fiber suspensions used for possible additional layers (such as a second outer layer and / or an additional intermediate layer), can be in the range of 10-25% by weight or 15-25% by weight, preferably 17-23% by weight. The ash content can, for example, be 10-20% by weight or 12-18% by weight. The ash content indicates a high amount of inorganic materials in the fiber suspension, which originate from fillers and / or residues of inorganic coating pigments associated with recycled fibers. In particular, fiber suspensions containing or composed of short cellulose fibers with a length-weighted average length <1.5 mm (preferably <1.2 mm) (measured using a Kajaani FS fiber length analyzer) can have an ash content of 15-25% by weight (preferably 17-23% by weight). The ash content of the fiber suspension is typically measured from a thick stock before a short cycle on the paperboard machine. The addition of glyoxylated polyacrylamide with a number-average molecular weight of at least 15,000 g / mol is particularly advantageous for fiber suspensions with high ash content, as it can provide the required internal strength in the z-direction.
[0036] According to one embodiment of the invention, the first fiber suspension and the second fiber suspension have different ash contents. The difference between the ash contents of the first fiber suspension and the second fiber suspension can be at least 2 percentage units, preferably at least 4 percentage units. According to one embodiment, measured from the thick stock after the machine chest, the ash content of the first fiber suspension can be 15-24%, and the ash content of the second fiber suspension can be 8-14%. Alternatively, for example, when using the US OCC, the ash content of the first fiber suspension can be 7-15%, and the ash content of the second fiber suspension can be 2-6%. Especially when the first and second fiber suspensions have different ash contents and contain cellulose fibers with different length-weighted average lengths, the adhesion between the resulting layers is generally quite low. However, according to the invention, the addition of specific glyoxylated polyacrylamide can significantly improve the adhesion between layers and reduce the risk of delamination even in this case.
[0037] The conductivity of the first and / or second fiber suspension and any additional fiber suspension (e.g. for the second outer layer or for possible additional intermediate layers) can be in the range of 2.5-10 mS / cm, preferably 3-8 mS / cm, and even more preferably 4-8 mS / cm.
[0038] According to one embodiment, the first fiber suspension may comprise or consist of virgin kraft pulp, virgin chemithermomechanical pulp, or mixtures thereof, while the second fiber suspension comprises or consists of recycled fibers (preferably broken fibers).
[0039] According to another embodiment, at least the first fiber suspension comprises or consists of mixed office waste pulp, wherein the first layer formed is a white top liner paper layer.
[0040] According to one embodiment of the invention, glyoxylated polyacrylamide is preferably added to a first, second, and / or any additional fiber suspension with a consistency of ≥1.6 wt% (preferably ≥2 wt%, more preferably ≥2.5 wt% or ≥3 wt%). The consistency of the fiber suspension can be in the range of 1.6-10 wt%, more preferably 2-4.5 wt% or 2.5-4.0 wt%. This means that adding glyoxylated polyacrylamide to a so-called thickened stock, especially when the fiber stock contains short cellulose fibers, allows for effective interaction between the polymer and the short cellulose fibers in the fiber suspension. The short cellulose fibers comprise cellulose fibers with a length-weighted average length <1.5 mm (preferably <1.2 mm) as measured using a Kajaani FSA fiber length analyzer.
[0041] According to one embodiment of the invention, when the fiber suspension contains long fibers with a length-weighted average length >1.5 mm (preferably >1.7 mm) as measured using a Kajaani FS fiber length analyzer, glyoxylated polyacrylamide can be added to a fiber suspension with a consistency <1.6 wt% (preferably <1 wt%). For example, glyoxylated polyacrylamide can be added to a fiber suspension with a consistency in the range of 0.1-1.5 wt% (preferably 0.2-0.9 wt%).
[0042] The amount of glyoxylated polyacrylamide added can be 0.5-5 kg / ton of dry fiber suspension, preferably 0.8-4 kg / ton of dry fiber suspension, and more preferably 1-3 kg / ton of dry fiber suspension. Different amounts of glyoxylated polyacrylamide can be added to each type of fiber suspension.
[0043] After adding glyoxylated polyacrylamide to a fiber suspension, the fiber suspension is used to form a first layer, a second layer, and any additional layers, which are combined with each other to form a multilayer web. Any suitable method and / or unit can be used to form the fiber layers and combine them before wet pressing the formed multilayer web. It is preferable to combine the layers when the dryness of each layer is <15% by weight. For example, the multilayer web can be formed from separate first, second, and additional layers by multiple separate forming units. Each layer is formed by its own forming unit with the associated fiber suspension, and then these layers are combined together. According to this embodiment, each layer is first formed separately on wire or the like, and then combined in a subsequent stage after at least partially draining these layers. The forming unit can include a headbox or a rotary screen forming machine. The formed multilayer web is then subjected to further drainage, wet pressing, and drying.
[0044] Alternatively, multi-layer slabs can be formed by using multi-layer headboxes.
[0045] According to yet another embodiment, the first fiber layer may be formed from a first fiber suspension, at least a portion of the water is drained from the first layer on the wire portion, and then a second layer is applied to the surface of the first web, and the assembled multilayer web is further drained, wet-pressed, and dried. The second fiber layer applied to the surface of the first layer does not need to be drained before the layers are assembled.
[0046] After the first layer, second layer, and any additional layers (such as additional intermediate layers) are combined together, the resulting multilayer board web is wet-pressed in the press section of a board machine. After wet pressing, the multilayer board web is dried, preferably to a dryness of at least 75% by weight, and typically to a dryness of 80-85% by weight.
[0047] The resulting multilayer board can have a basis weight of at least 70 g / m². 2 Preferably at least 85g / m 2 More preferably at least 100g / m 2 Or at least 120g / m 2 The weight can be, for example, 70-800 g / m³. 2 Within the range, 85-700 g / m³ is preferred. 2 More preferably 100-300g / m 2 , or even better, 120-150g / m 2 The multilayer board provided by this invention exhibits good resistance to delamination or splitting even at high basis weights. The multilayer board can be selected from test linerboard, grooved board, white top linerboard, gypsum board linerboard, or core board linerboard. According to a preferred example, the basis weight of one of the layers (e.g., the top or outer layer of corrugated board) can be 35-80 g / m². 2 .
[0048] According to a preferred embodiment, a size solution can be applied to one or both surfaces of the multilayer sheet after drying. Impregnating the first and / or second layers of the multilayer sheet with the size solution enhances the z-direction strength of the multilayer sheet. The size solution may contain starch or polyvinyl alcohol, preferably starch. Especially when the size solution contains starch, the starch can react with glyoxylated polyacrylamide within the layers, thereby providing an increased strength effect to the final multilayer sheet, including both internal z-direction strength and surface strength. Therefore, the present invention provides an advantageous effect because, otherwise, when applied using a metering sizing press, the size starch typically only penetrates from the surface by an average of about 30 g / m². 2 This increases the risk of interlayer delamination. According to a preferred embodiment, the surface sizing solution contains degraded starch. When the surface sizing solution contains starch or degraded starch, its application amount, calculated based on the weight of the multilayer board, can be 1-12% by weight, preferably 1-10% by weight, more preferably 2-8% by weight, and even more preferably 3-7% by weight.
[0049] The manufacture of multi-layer boards does not require any creping step using Yankee drying cylinders before or after the multi-layer board is dried. After drying, the resulting multi-layer boards can be corrugated in conventional corrugating machines used to manufacture corrugated board.
[0050] According to one embodiment, the resulting multilayer board can be used as a backing paper for gypsum board. The multilayer board can be adhered to the large surface of the gypsum board. The improved anti-delamination properties make the board particularly suitable for this end use. Detailed Implementation
[0051] experiment
[0052] The following non-limiting examples describe some embodiments of the invention.
[0053] Example 1
[0054] Example 1 demonstrates the effect of high number-average molecular weight glyoxylated polyacrylamide on the performance of multilayer boards.
[0055] chemicals
[0056] Table 1 shows the glyoxylated polyacrylamides tested. The peak molecular weights in Table 1 indicate the molecular weight at the peak of the distribution curve, i.e., the molecular weight of the largest population of the polymer. GPAM1 and GPAM2 are commercially available glyoxylated polyacrylamides and are used as references.
[0057] Table 1. Parameters of the tested polymers.
[0058]
[0059] As can be seen from Table 1, even though the weight-average molecular weight of reference GPAM2 is similar to that of iGPAM1 and iGPAM2, the number-average molecular weight of GPAM2 is much lower than that of iGPAM1 and iGPAM2. This also applies to GPAM1.
[0060] Fiber suspension, formation of multilayer boards
[0061] Two-layer multilayer sheets were prepared using two different fiber suspensions. The first fiber suspension for the top layer was prepared from long-fiber recycled corrugated cardboard (OCC) with a length-weighted fiber length of 1.4 mm (measured using a Kajaani FSA fiber length analyzer) and an ash content of 16% measured at 525°C. The second fiber suspension for the back layer was prepared from short-fiber OCC with a length-weighted fiber length of 1.2 mm and an ash content of 16%, with measurements identical to the first layer.
[0062] Long-fiber OCC and short-fiber OCC were wet-lysed separately at 70°C using a Noviprefibre pulper (20 L / L) to a consistency of 3 wt%, at 500 rpm for 30 s and 1000 rpm for 25 min, without soaking. The resulting fiber suspension was further diluted with tap water to a consistency of 0.6 wt%. The pH and conductivity of the fiber suspension were adjusted to 6.8 and 3.0 mS / cm, respectively. To adjust the conductivity, a salt mixture containing 70 wt% calcium acetate, 20 wt% sodium sulfate, and 10 wt% sodium bicarbonate was added until the target conductivity was achieved.
[0063] Multilayer sheets were formed using a Dynamic Sheet Forming (DSF) machine. Chemicals were added to the mixing tank of the DSF, and the same chemicals were added to the first and second fiber suspensions. Glyoxylated polyacrylamide from Table 1 was used in the experiments at an addition level of 2.5 kg / ton. Addition levels are given in kg of dry chemicals per ton of dry OCC fiber suspension. Each experiment included the addition of a retention aid system of cationic polyacrylamide (100 g / t) and silica (400 g / t).
[0064] The following forms sheet materials:
[0065] First, a second fiber suspension for the backing layer is added to the DSF and sprayed to form the backing layer. Before draining, a top layer is formed on the backing layer using the first fiber suspension. Water is drained after both fiber suspensions are sprayed. The roller speed is 1250 rpm, the pulp mixer speed is 450 rpm, the pulp pump speed is 950 rpm / min, the sweeping number is 100, and the scooping time is 60 s. The multilayer sheet is removed from the roller and placed between the filament and one absorbent paper on the other side of the sheet. The wet absorbent paper and filament are removed, and the sheet is wet-pressed on a Techpap grooved press at 5 bar pressure, undergoing two wet pressings, with a new absorbent paper placed on each side of the sheet before each pressing. The sheet is dried under confined conditions in a roller dryer. The roller temperature is adjusted to 92°C, and the throughput time is 1 min. Four passes are performed: the first two passes place the sheet between absorbent papers, and the second pass does not.
[0066] The weight of each layer is 70g / m³. 2 Therefore, the total weight of the sheet is 140 g / m². 2 .
[0067] According to standard ISO 187, the sheet is pre-conditioned at 23°C and 50% relative humidity for 24 hours.
[0068] After preconditioning, the sheets are cut. The first portion of the sheet was tested for strength properties without surface sizing, while the second portion of the sheet was surface sizinged before strength property testing.
[0069] Surface sizing was performed using a degraded starch solution. The starch solution was a mixture of C*Film 07311 and C*Film 07312 (50 wt% + 50 wt%) dextrin starch. The sizing solution concentration was 10 wt% at all test points. The solution was kept at 70°C before use, and approximately 170 g of solution was applied to the surface at each test point. The starch solution was applied using a Mathis laboratory sizing press, and the sizing sheets were then roller-dried. The sizing press was washed between test points. Surface sizing was performed on 5 A5-sized sheets at each test point. Table 2 shows the sizing press and drying parameters.
[0070] After surface sizing and drying, the sheets are placed in a climate-controlled laboratory (50% relative humidity, 23°C) for conditioning.
[0071] Table 2. Laboratory sizing press and drying parameters used in the preparation of multilayer board sheets.
[0072]
[0073]
[0074] After conditioning, the strength characteristics of the multilayer sheet, including SCT (short span compressive strength), burst strength, tensile strength, and internal bond strength, were measured. Table 3 shows the apparatus and standards used. Table 4 shows the measurement results for multilayer sheets without surface sizing, and Table 5 shows the measurement results for surface-sizing sheets.
[0075] Table 3 shows the sheet testing equipment and standard methods used.
[0076] Measurement Device standard Basis weight Mettler Toledo ISO 536 Short Span Compression Test (SCT) Lorentzen & Wettre ISO 9895 Tension strength Lorentzen & Wettre ISO 2758 Internal bonding Huygen Internal Scott Bond Tester TAPPI T569 Tensile strength Lorentzen & Wettre ISO 1924-3
[0077] Table 4 shows the results for multilayer boards without surface adhesive.
[0078]
[0079] Table 5 shows the results for multilayer sheets with surface adhesive.
[0080]
[0081]
[0082] As shown in Table 4, iGPAM1 and iGPAM2, with their high number-average molecular weight, generally offer higher strength values than conventional GPAM1 and GPAM2. In particular, the improved tensile index in the machine direction reduces surface cracking before application, thereby improving overall machine efficiency.
[0083] As shown in Table 5, combining iGPAM1 and iGPAM2, with their high number-average molecular weight, with surface sizing agents provides an unexpected increase in strength properties compared to conventional GPAM1 and GPAM2. The lower charge density of iGPAM1 appears to be particularly beneficial for improving internal adhesion, a crucial performance characteristic of processing steps such as corrugation and printing. For test liners using lower-strength recycled fiber fillers, even when sizing and pressing are used solely to reinforce the test liners instead of kraft paperboard, it is difficult to achieve similar internal adhesion strength as kraft paperboard made from higher-strength virgin fibers. The improved tensile strength obtained with iGPAM1 also reduces folding cracks at the edges of corrugated boxes.
[0084] Even though the invention has been described with reference to what appears to be the most practical and preferred embodiments, it should be understood that the invention is not limited to the embodiments described above, but is also intended to cover different modifications and equivalent technical solutions within the scope of the appended claims.
Claims
1. A method for manufacturing multilayer boards in a paperboard machine, preferably for improving the delamination resistance of the multilayer board, the multilayer board comprising at least two layers, the method comprising: - Obtain a first fiber suspension containing cellulose fibers for the first layer and a second fiber suspension containing cellulose fibers for the second layer, wherein... The first fiber suspension and the second fiber suspension are different from each other, and at least one of them contains recycled cellulose fibers; - The first layer is formed from the first fiber suspension, and the second layer is formed from the second fiber suspension. - By combining the first layer and the second layer with each other to form a multilayer sheet, the multilayer sheet is then wet-pressed in the press section of the paperboard machine. -Dry the multilayer sheet. Its features - Before forming the first layer and the second layer, add glyoxylated polyacrylamide with a number average molecular weight of at least 15,000 g / mol to the first fiber suspension and / or the second fiber suspension.
2. The method according to claim 1, characterized in that... After drying, the surface sizing solution is applied to one or both surfaces of the multilayer paperboard web.
3. The method according to claim 1 or 2, characterized in that... The glyoxylated polyacrylamide has a number average molecular weight in the range of 15,000-250,000 g / mol, preferably 20,000-200,000 g / mol, more preferably 25,000-150,000 g / mol, and even more preferably 30,000-100,000 g / mol.
4. The method according to claim 1, 2 or 3, characterized in that... Based on the total amount of glyoxal and polyacrylamide, the total glyoxal content of free glyoxal and reacted glyoxal in the acetaldehyde-acidified polyacrylamide is in the range of 5-25% by weight, preferably 7-21% by weight, more preferably 9-18% by weight, and even more preferably 10-17% by weight.
5. The method according to any one of claims 1-4, characterized in that... The charge density of the glyoxylated polyacrylamide, measured at pH 7, is in the range of 0.4-2.5 meq / g, preferably 0.7-2.2 meq / g, more preferably 0.9-2.0 meq / g, and even more preferably 1.0-1.7 meq / g.
6. The method according to any one of claims 1-5, characterized in that... The ash content of the first fiber suspension and / or the second fiber suspension is in the range of 15-25% by weight, preferably 17-23% by weight.
7. The method according to any one of claims 1-6, characterized in that... The conductivity of the first fiber suspension and / or the second fiber suspension is in the range of 2.5-10 mS / cm, preferably 3-8 mS / cm, and more preferably 4-8 mS / cm.
8. The method according to any one of claims 1-7, characterized in that... The cellulose fibers in the first fiber suspension have a first length-weighted average length, and the cellulose fibers in the second fiber suspension have a second length-weighted average length, wherein the first length-weighted average length and the second length-weighted average length are different from each other.
9. The method according to claim 8, characterized in that... The first length-weighted average length and the second length-weighted average length have a difference in the range of 0.1-1.5 mm.
10. The method according to claim 8 or 9, characterized in that... The first length-weighted average length is in the range of 0.8-1.2 mm, and the second length-weighted average length is >1.2 mm to 2.0 mm.
11. The method according to claim 8 or 9, characterized in that... The first length-weighted average length is in the range of 1.0-1.5 mm, and the second length-weighted average length is >1.5 mm to 2.5 mm.
12. The method according to any one of claims 1-11, characterized in that... The glyoxylated polyacrylamide is added to either the first fiber suspension or the second fiber suspension.
13. The method according to any one of claims 1-11, characterized in that... The glyoxylated polyacrylamide is added to the first fiber suspension and the second fiber suspension.
14. The method according to any one of claims 1-13, characterized in that... The amount of glyoxylated polyacrylamide added is 0.5-5 kg / ton of dry fiber suspension, preferably 0.8-4 kg / ton of dry fiber suspension, and more preferably 1-3 kg / ton of dry fiber suspension.
15. The method according to any one of claims 1-14, characterized in that... The basis weight of the multilayer board is at least 70 g / m². 2 Preferably at least 85g / m 2 More preferably 85-700g / m 2 Within the range, or even more preferably 100-300g / m 2 Or 120-150g / m 2 .
16. The method according to any one of claims 1-15, characterized in that... The multilayer board is a test linerboard, grooved board, white top linerboard, gypsum board linerboard, or core board linerboard.
17. The method according to any one of claims 1-16, characterized in that... The surface sizing solution contains degraded starch, and the amount applied is 1-12% by weight, preferably 1-10% by weight, more preferably 2-8% by weight, and even more preferably 3-7% by weight, based on the weight of the multilayer board.
18. The method according to any one of claims 1-17, characterized in that... The glyoxylated polyacrylamide is added to the first fiber suspension and / or the second fiber suspension with a consistency of >1.6% by weight, preferably ≥2% by weight, more preferably ≥3% by weight.